1983
DOI: 10.1002/ddr.430030203
|View full text |Cite
|
Sign up to set email alerts
|

Mescaline‐induced head‐twitches in the rat: An in vivo method to evaluate serotonin S2 antagonists

Abstract: An intravenous dose of 20.0 mg/kg of mescaline induced a reproducible head-twitch response in rats. Drugs with very different pharmacological activities were tested for potential inhibition of this response. Among these drugs were a large number of serotonin antagonists, including several members of the recently described selective Sp antagonists of which ketanserin (a potent vascular Sp antagonist) and pirenperone (a pure LSD antagonist) are two prototypes. The same compounds were further studied in six in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…None of the antagonists caused head shakes when given alone. Calculated ID50 values are given in Table 2 and were in order: metergoline = ketanserin < altanserin < ritanserin < mianserin < pizotifen < methysergide = LY The present findings strengthen previous evidence (Kennett & Curzon, 1988a) (Bedard & Pycock, 1977;Yap & Taylor, 1983;Niemegeers et al, 1983).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…None of the antagonists caused head shakes when given alone. Calculated ID50 values are given in Table 2 and were in order: metergoline = ketanserin < altanserin < ritanserin < mianserin < pizotifen < methysergide = LY The present findings strengthen previous evidence (Kennett & Curzon, 1988a) (Bedard & Pycock, 1977;Yap & Taylor, 1983;Niemegeers et al, 1983).…”
Section: Discussionsupporting
confidence: 88%
“…We have now minimized the above problems by comparing the ratios of in vivo ID50 values of ten antagonists against mCPP-induced hypophagia and 5-HT2-mediated (Bedard & Pycock, 1977;Yap & Taylor, 1983;Niemegeers et al, 1983) head shakes with the corresponding ratios of in vitro drug affinities for various 5-HT1 receptor subtypes and 5-HT2 receptors. This provides indices of blockade of different 5-HT receptors which are independent of differences in drug absorption or metabolism and which can be compared with published in vitro affinity ratios.…”
mentioning
confidence: 99%
“…It has been reported that the 5-HT agonist mescaline-induced head-twitches are inhibited by various 5-HT antagonists including the selective 5-HT2 receptor antagonists ketanserin and pirenperone and that antagonism of mescaline correlates with inhibition of [3H]spiperone binding to the rat prefrontal cortex in vitro (4). These findings indicate that the head-twitches induced by mes caline are mediated by central 5-HT2 receptors.…”
mentioning
confidence: 76%
“…been identified as a particular target in an attempt to reduce EPS liability (39,49,58,83). Since iloperidone inhibits binding to 5-HTzA receptors in vitro, it was tested for inhibition of 5-HTP-induced head twitch, a 5-HT2 receptor-mediated behavior (52,53,68,71). Iloperidone inhibits head twitch (EDSo = 0.07 mg/kg i. p.), consistent with its affinity for 5-HT2 receptors, indicating that iloperidone blocks 5-HT2 receptors in vivo.…”
Section: Eps Liabilitymentioning
confidence: 99%